Risk Management in Improving Accountability of Regional Head Election Grant Funds - Muhadam Labolo; Nurliah Nurdin; Layla Kurniawati; Rini Wartini (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Regional Head Elections in Indonesia face complex challenges in managing grant funds, marked by operational risks, regulatory fragmentation, and accountability gaps. This study aims to analyze risk management practices in these elections and propose a tailored framework to enhance transparency and accountability. Using a qualitative descriptive-analytical approach, data were collected through interviews with election officials, regional finance officers, and inspectorates, alongside documentation studies and observations in selected regions during the 2024 elections. Findings reveal that human resource deficiencies, security threats, and natural disaster vulnerabilities, coupled with misaligned fiscal-electoral cycles and inconsistent regulations, hinder effective grant fund governance. Cases of fund misuse, such as fictitious expenditures, highlight weak internal controls and low risk management knowledge among organizers. A proactive risk-intelligent approach, integrating harmonized regulations, multi-stakeholder risk committees, and digital monitoring systems, is essential to address these issues. This study concludes that a context-specific risk management framework can strengthen accountability, reduce irregularities, and foster public trust in Regional Head Elections, contributing to democratic integrity.